Efektivitas dan Kelemahan Autentikasi Berbasis Web Menggunakan One-Time Password (OTP) dalam Mencegah Akses Tidak Sah - Fajar Maulana; Yomei Hendra; Putri Sakinah; Yofhanda Septi Eirlangga; Aisyah Qurrata Ayun (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Authentication based on one-Time Password (OTP) is one method that is widely used in securing access to web systems. This study aims to analyze in depth the effectiveness and weaknesses of the OTP authentication system in preventing unauthorized access. Through a qualitative approach based on literature studies, as well as comparisons between other authentication methods, it was found that OTP is able to increase a significant additional layer of security, especially when combined with other authentication methods such as passwords or biometrics. However, this system still has various weaknesses, such as the risk of phishing attacks, man-in-the-middle (MITM) attacks, and vulnerabilities to SIM swapping attacks, especially in the implementation of OTP via SMS. Dependence on user devices and communication networks is also a limiting factor in the effectiveness of OTP. This study provides recommendations for the implementation of strengthening measures such as Multi-Factor Authentication (MFA), the use of authenticator applications, and the implementation of end-to-end encryption to reduce security risks. The results of this study are expected to be a reference for system developers and organizations in choosing and implementing authentication methods that are more secure and in accordance with current cybersecurity needs.